Skeletal muscle‐specific eukaryotic translation initiation factor 2α phosphorylation controls amino acid metabolism and fibroblast growth factor 21‐mediated non‐cell‐autonomous energy metabolism. Issue 2 (20th October 2015) - Miyake, Masato; Nomura, Akitoshi; Ogura, Atsushi; Takehana, Kenji; Kitahara, Yoshihiro; Takahara, Kazuna; Tsugawa, Kazue; Miyamoto, Chinobu; Miura, Naoko; Sato, Ryosuke; Kurahashi, Kiyoe; Harding, Heather P.; et al.
Abstract : The eukaryotic translation initiation factor 2a (eIF2α) phosphorylation‐dependent integrated stress response (ISR), a component of the unfolded protein response, has long been known to regulate intermediary metabolism, but the details are poorly worked out. We report that profiling of mRNAs of transgenic mice harboring a ligand‐activated skeletal muscle–specific derivative of the eIF2α protein kinase R‐like ER kinase revealed the expected up‐regulation of genes involved in amino acid biosynthesis and transport but also uncovered the induced expression and secretion of a myokine, fibroblast growth factor 21 (FGF21), that stimulates energy consumption and prevents obesity. The link between the ISR and FGF21 expression was further reinforced by the identification of a small‐molecule ISR activator that promoted Fgf21 expression in cell‐based screens and by implication of the ISR‐inducible activating transcription factor 4 in the process. Our findings establish that eIF2α phosphorylation regulates not only cell‐autonomous proteostasis and amino acid metabolism, but also affects non‐cell‐autonomous metabolic regulation by induced expression of a potent myokine.—Miyake, M., Nomura, A., Ogura, A., Takehana, K., Kitahara, Y., Takahara, K., Tsugawa, K., Miyamoto, C., Miura, N., Sato, R., Kurahashi, K., Harding, H. P., Oyadomari, M., Ron, D., Oyadomari, S. Skeletal muscle‐specific eukaryotic translation initiation factor 2a phosphorylation controls amino acid metabolism and fibroblast growth factor 21‐mediated non‐cell‐autonomous energy metabolism. FASEB J. 30, 798–812 (2016). www.fasebj.org